Elimination of Discrimination Against Women & CEDAW: to What Extent is it Jus Cogens? - Rr Kunti Dewi Adriane Kusumowardono (Universitas Airlangga, 2023)
The international community gathers on occasion to try and achieve specific purposes, through the development of a system of guidance, norms and regulations for States to observe, commonly called international law. There have been many achievements by the international community working together for the collective interests of the States, for example through the creation of human rights law. Many international treaties have been passed that bind the States to achieve the desired collective purposes. One of these is the Convention on The Elimination of All Forms of Discrimination Against Women, which departs from the fundamental norms set by the United Nations Charter as well as the Universal Declaration of Human Rights about equality between the rights of men and women for their dignity and freedom. However, several States that are party to the Convention have reserved some of the articles, and there is some controversy around it. Therefore, it is the purpose of this article to analyse whether the concept of eliminating discrimination against women and the values and norms contained in CEDAW can be categorised as Jus Cogens norms, in view of the fact that it is a manifestation of the human rights values agreed upon by the international community. Moreover, this article will also analyse the Convention’s implications on domestic norms in States with significant reservations to the Convention.